The Cult of Saints in Central Asia (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Scholars specializing in classical Oriental studies as well as contemporary writers pay great attention to the origins, development, and status of the saint veneration. By analyzing the characteristics of retained remnants of the pre-Islamic substrate and their influence on the contemporary palette of religious groups in Uzbekistan, this article addresses the issue, which is pertinent to modern Islamic studies.